2010
DOI: 10.1136/thx.2009.132696
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral airway/alveolar sites of exhaled nitric oxide in acute asthma

Abstract: Introduction Central airway nitric oxide flux (J' awNO ) and peripheral airway/alveolar nitric oxide concentration (C ANO ) during asthma exacerbation has not been investigated after correction for axial NO back-diffusion. Methods After measuring exhaled NO (fraction of exhaled nitric oxide (F E NO); ppb) at 50, 100, 150 and 200 ml/s, J' awNO (nl/s) and C ANO (ppb) were calculated using the two-compartment model and corrected for axial NO back-diffusion. Fifteen (8 males), non-smoking, patients with moderate-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 37 publications
(95 reference statements)
5
30
1
1
Order By: Relevance
“…One study found no increased alveolar NO levels during an exacerbation. 38 Two studies demonstrated no association between alveolar NO values and ACQ scores. 28,29 The studies of Oosterhoff et al 42 ACT, Asthma Control Test; BDI, Baseline Dyspnea Index; CC, closing capacity; CT, computed tomography; CV, closing volume; dN2, slope of phase III of SBNT; FOT, forced oscillation technique; FRC, functional residual capacity; FVC, forced vital capacity; IC, inspiratory capacity; R5, resistance of the respiratory system at 5 Hz; R20, resistance of the respiratory system at 20 Hz; R5-R20, difference of R5 and R20; Rp, peripheral lung resistance; SF6, sulfur hexafluoride; VC, vital capacity; X5, reactance of the respiratory system at 5 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…One study found no increased alveolar NO levels during an exacerbation. 38 Two studies demonstrated no association between alveolar NO values and ACQ scores. 28,29 The studies of Oosterhoff et al 42 ACT, Asthma Control Test; BDI, Baseline Dyspnea Index; CC, closing capacity; CT, computed tomography; CV, closing volume; dN2, slope of phase III of SBNT; FOT, forced oscillation technique; FRC, functional residual capacity; FVC, forced vital capacity; IC, inspiratory capacity; R5, resistance of the respiratory system at 5 Hz; R20, resistance of the respiratory system at 20 Hz; R5-R20, difference of R5 and R20; Rp, peripheral lung resistance; SF6, sulfur hexafluoride; VC, vital capacity; X5, reactance of the respiratory system at 5 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…22 In 13 of the 15 evaluated adults with asthma, there was increased NO flux in predominantly central airway sites in patients with clinically stable, moderate-to-severe asthma at baseline with abnormal spirometry despite moderatedose ICS and long-acting b 2 -agonist (LABA). 23 NO production in central airway sites was further increased in the same 13 of the 15 patients during exacerbation prior to the initiation of oral corticosteroid with robust clinical and spirometric response following an 8-day tapering course. The absence of increased C ANO was in contrast to our previous observations of increased C ANO in patients with clinically stable asthma 13,14 even after correction for axial NO back-diffusion.…”
mentioning
confidence: 93%
“…None of the above asthma studies [8][9][10][11][13][14][15][16][17][18][19][20][21] corrected for NO axial back-diffusion. 12, 22 Gelb et al 23 recently reported outpatient studies in acute asthma using the 2-compartment NO model 11 back-diffusion of NO. 22 In 13 of the 15 evaluated adults with asthma, there was increased NO flux in predominantly central airway sites in patients with clinically stable, moderate-to-severe asthma at baseline with abnormal spirometry despite moderatedose ICS and long-acting b 2 -agonist (LABA).…”
mentioning
confidence: 98%
“…Figure 1b shows data from 15 interventional studies in asthma patients [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] including five studies (solid symbols and lines) where two treatment arms were compared, either within the same group of asthma patients or between two comparable patient groups [6][7][8][9][10][11]. It can be seen that the majority of studies follows the ''normal'' CA,NO decrease with respect to J9aw,NO decrease, in which case the treatment effectively lowers bronchial nitric oxide production but does not really affect alveolar nitric oxide when taking into account the back-diffusion effect.…”
mentioning
confidence: 99%